Synthesis and Characterization of Mixed Iron-Manganese Oxide Nanoparticles and Their Application for Efficient Nickel Ion Removal from Aqueous Samples - Alessandro Buccolieri; Antonio Serra; Giuseppe Maruccio; Anna Grazia Monteduro; Sanosh Kunjalukkal Padmanabhan; Antonio Licciulli; Valentina Bonfrate; Luca Salvatore; Daniela Manno; Lucio Calcagnile; Gabriele Giancane (Journal of Analytical Methods in Chemistry)
Mixed iron-manganese oxide nanoparticles, synthesized by a simple procedure, were used to remove nickel ion from aqueous solutions. Nanostructures, prepared by using different weight percents of manganese, were characterized by transmission electron microscopy, selected area diffraction, X-ray diffraction, Raman spectroscopy, and vibrating sample magnetometry. Adsorption/desorption isotherm curves demonstrated that manganese inclusions enhance the specific surface area three times and the pores volume ten times. This feature was crucial to decontaminate both aqueous samples and food extracts from nickel ion. Efficient removal of Ni2+ was highlighted by the well-known dimethylglyoxime test and by ICP-MS analysis and the possibility of regenerating the nanostructure was obtained by a washing treatment in disodium ethylenediaminetetraacetate solution.